(36÷4-72÷9)÷(70÷7-45÷5-2×0)=
Răspunsuri la întrebare
Răspuns de
4
(36÷4-72÷9)÷(70÷7-45÷5-2×0)=
=(9-8):(10-9-0);
=1:1;
=1;
Răspuns de
2
( 36 : 4 - 72 : 9 ) : ( 70 : 7 - 45 : 5 - 2 × 0 ) =
( 9 - 72 : 9 ) : ( 70 : 7 - 45 : 5 - 2 × 0 ) =
( 9 - 8 ) : ( 70 : 7 - 45 : 5 - 2 × 0 ) =
1 : ( 70 : 7 - 45 : 5 - 2 × 0 ) =
1 : ( 10 - 45 : 5 - 2 × 0 ) =
1 : ( 10 - 9 - 2 × 0 ) =
1 : ( 10 - 9 - 0 ) =
1 : ( 1 - 0 ) =
1 : 1 =
1
* Rezultatul final este - 1.
Alte întrebări interesante
Istorie,
8 ani în urmă
Limba română,
8 ani în urmă
Engleza,
8 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă